2012
DOI: 10.1155/2012/829608
|View full text |Cite
|
Sign up to set email alerts
|

Near Fatal Asthma: Clinical and Airway Biopsy Characteristics

Abstract: Background. Inflammation and remodeling are integral parts of asthma pathophysiology. We sought to describe the clinical and pathologic features of near fatal asthma exacerbation (NFE). Methods. Bronchial biopsies were collected prospectively from NFE I subjects. Another NFE II group and a moderate severity exacerbation control group (ME II) were retrospectively identified—no biopsies obtained. Results. All NFE II (n = 9) subjects exhibited remodeling and significant inflammation (eosinophilic, neutrophilic). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In asthma, the airway wall thickens in proportion to disease severity and duration 50,51 . This remodelling involves an increase in airway smooth muscle, thickening of the subepithelial reticular lamina, matrix deposition throughout the airway wall, angiogenesis, neuronal proliferation and epithelial mucous metaplasia -a process that involves the appearance of mucous cells in new areas of the airways and increased production of mucus (FIG.…”
Section: Airway Remodellingmentioning
confidence: 99%
“…In asthma, the airway wall thickens in proportion to disease severity and duration 50,51 . This remodelling involves an increase in airway smooth muscle, thickening of the subepithelial reticular lamina, matrix deposition throughout the airway wall, angiogenesis, neuronal proliferation and epithelial mucous metaplasia -a process that involves the appearance of mucous cells in new areas of the airways and increased production of mucus (FIG.…”
Section: Airway Remodellingmentioning
confidence: 99%
“…This situation differs from that of conventional asthma, which is characterized by eosinophil infiltration [12,13]. Neutrophil elastase (NE) generated by neutrophils has been shown to be a potent mucin secretagogue [14].…”
Section: Introductionmentioning
confidence: 99%
“…16 Studies of fatal or near-fatal asthma have indicated that increased inflammation during exacerbations aggravates this chronic state, causing pronounced mucus oedema, and lumen occlusion by mucus plugs, in a setting of predominantly eosinophilic infiltration. [17][18][19] In light of this, even subtle changes in oxygenation could represent differences in the pathology involved and prove to be of prognostic value, but further studies are required to investigate this.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic airway inflammation is associated with more pronounced airway smooth muscle hypertrophy, and severe asthma in general is known to be associated with pronounced structural changes in the peripheral airways . Studies of fatal or near‐fatal asthma have indicated that increased inflammation during exacerbations aggravates this chronic state, causing pronounced mucus oedema, and lumen occlusion by mucus plugs, in a setting of predominantly eosinophilic infiltration . In light of this, even subtle changes in oxygenation could represent differences in the pathology involved and prove to be of prognostic value, but further studies are required to investigate this.…”
Section: Discussionmentioning
confidence: 99%